Operationalizing resilience planning, theory, and practice: Insights from U.S. seaports - Kalaidjian, Ellis; Becker, Austin; Pinel, Sandra (Frontiers in Sustainability, 2022)
Academics and practitioners advocate climate change resilience planning to guide seaport management, business continuity planning, capital improvements, and so forth. Yet, questions of whether resilience planning interventions influence seaports’ planning cultures and result in better prepared organizations remain underexplored. Through 10 cases of U.S. seaport resilience planning, this research explored the benefits and challenges of resilience planning and whether such efforts can enhance the adaptive capacity of a complex, multi-layered system such as a seaport. Results suggested that resilience planning interventions enhanced, inter alia, seaports’ social capital with their internal and external stakeholders, and that seaports frequently identified and pursued infrastructure-related resilience enhancement strategies after completing resilience planning. Even when the sponsors of such studies intended an operational and business resilience purpose, they stated benefits consistent with adaptive management and resilience planning theories. Further, while key informants emphasized the strengthened relationships with stakeholders as benefits, they also frequently cited them as key challenges that require deliberative guidance and resources to help stakeholders effectively use products from resilience planning. Additional takeaways captured in this research provide valuable insights that can inform guidance materials designed to help seaports undertake their climate resilience-building endeavors.